Business Governance and Collaboration in Village-Owned Enterprises (BUMDes) in Efforts to Improve Market Performance in The Madiun Residential - Maduwinarti, Ayun; Taali , Muhammad (International Journal of Social and Management Studies, 2023)
During the Covid-19 pandemic, almost all economic sectors are experiencing a downturn, so the district and city governments in Madiun are taking tactical steps, namely accelerating economic recovery through optimizing Village-Owned Enterprises (BUMDes) and Micro, Small, and Medium Enterprises (UMKM). which is seen as effective in sustaining the community's economy. So this research wants to examine the governance of BUMDes, which drives alliance business collaboration with MSMEs and other business managers to improve marketing performance. Descriptive quantitative research collected data using a questionnaire that was distributed to 78 administrators and documented data on the management of BUMDes and UMKM in the Madiun area. The results of the descriptive statistical analysis show that the management of BUMDes to improve market performance is carried out by strengthening collaboration with UMKM, using IT and innovation in the procurement of joint business stalls. Business collaboration with UMKM and individual businesses has also proven capable of improving marketing performance, which since collaboration has increased profitability, expanded marketing areas, and increased the number of market segments. So it can be concluded that improving business governance and alliance business collaboration driven by BUMDes can improve marketing performance.